ANALISIS DETERMINAN AGRESIVITAS PAJAK PERUSAHAAN MANUFAKTUR - Indira Shinta Dewi; Nia Tresnawaty (Jurnal Liabilitas, 2023)
By using earnings management proxies, company size, and company liquidity, empirical data on how tax aggression affects manufacturing companies in Indonesia. between 2018 and 2022, the Indonesia Stock Exchange will be the main focus. Data processing uses Statistical Product and Service Solution for Windows version 24 (SPSS 24) and Microsoft Excel.Purposive sampling was used to collect 211 data. Multiple regression analysis is a data analysis method. The findings of the analysis show that liquidity has an impact on tax aggression more than firm size and earnings management. Based on the results of the F test, firm size, liquidity, and earnings management all have an effect on tax aggression. Keywords: Profit Manajemen, Company Size,Liquidity And Tax Aggressiveness